1998
DOI: 10.1086/515622
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Carriage of Neisseria meningitidis in a Group of Military Recruits: Subtype Stability and Specificity of the Immune Response following Colonization

Abstract: Meningococcal carriage and the immune response to colonization were studied in a group of military recruits undergoing basic training. Subtyping by determination of the class 1 protein sequence clearly differentiated between strains and demonstrated the dynamics of carriage and transmission. Expression of class 1 protein by each strain remained stable during prolonged carriage by different subjects. Following colonization, a marked increase in serum bactericidal response occurred, which was specific for the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
50
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 29 publications
9
50
1
Order By: Relevance
“…Homologous and heterologous antibodies to the other major OM porin PorB (spot 11) were also detected following colonization. The patterns of immunoreactivity to both porins observed in the current study support the results of previous studies that reported a correlation between bactericidal activity and an increase in antiporin antibodies in response to both meningococcal infection (17,58) and colonization (23,26). This result is also in accord with the observation that a subset of antibodies directed against PorA and PorB show heterologous as well as serosubtype specificity (58).…”
Section: Discussionsupporting
confidence: 92%
“…Homologous and heterologous antibodies to the other major OM porin PorB (spot 11) were also detected following colonization. The patterns of immunoreactivity to both porins observed in the current study support the results of previous studies that reported a correlation between bactericidal activity and an increase in antiporin antibodies in response to both meningococcal infection (17,58) and colonization (23,26). This result is also in accord with the observation that a subset of antibodies directed against PorA and PorB show heterologous as well as serosubtype specificity (58).…”
Section: Discussionsupporting
confidence: 92%
“…Protective antibodies to N. meningitidis group C strains can be directed at a number of antigenic targets, including the capsular polysaccharide or noncapsular antigens, such as PorA (18) or Opc (class 5 outer membrane proteins) (31). Based on absorption studies of gamma globulin prepared from more than 2,000 North American donors, Goldschneider et al concluded that the majority of naturally acquired group C serum bactericidal activity was directed against the capsular polysaccharide (10), which is consistent with our absorption data on individual sera.…”
Section: Discussionmentioning
confidence: 99%
“…However, porA may be a more appropriate target than ctrA for PCR-based detection of meningococcal carriage. In addition, porA PCR would enable the determination of subcapsular antigens, which have been associated with the development of specific immunity (9).…”
Section: Discussionmentioning
confidence: 99%